(untitled) (Global Journal of Human-Social Science, 1970)
The article examines the main features of the development of the digital economy in the developed countries of the world Some aspects of the introduction of digital currencies the impact of the digitalization process on the financial system and monetary policy of different countries are reflected and the possibilities of legal regulation of the use of digital financial assets in developed countries of the world are highlighted As a result of the research a review of scientific practical statistical information was made and the author s conclusions were given